Ultrashort-T2* mapping at 7 tesla using an optimized pointwise encoding time reduction with radial acquisition (PETRA) sequence at standard and extended echo times - Carly A. Lockard; Bruce M. Damon; Hacene Serrai (PLoS ONE, 2025)
Zero echo time (ZTE) sequences capture signal from tissues with extremely short T 2 * and are useful for qualitative and quantitative imaging of musculoskeletal tissues’ ultrashort-T 2 * components. One such sequence is Pointwise Encoding Time Reduction with Radial Acquisition (PETRA). While this sequence has shown promising results, it has undergone only limited testing at 7 tesla (T). The purpose of this work was to evaluate PETRA at 7T in its standard, commercially available form and with sequence code modifications to allow extended echo times for the purpose of performing ultrashort-T 2 * mapping. We acquired PETRA images of MnCl 2 and collagen phantoms and of the knee in eight participants (5 for optimization and 3 for ultrashort-T 2 * mapping assessment; 5 male/3 female, 39 ± 11 years old). Images were acquired using a 1-transmit/28-receive-channel knee coil. Artifacts, signal, signal-to-noise ratio (SNR), ultrashort-T 2 *, the corresponding curve fit quality, and repeatability were assessed. In knee tissues, SNR was higher at TE = 0.07 msec than in a conventional-TE sequence (Dual-Echo Steady State with TE = 2.55 msec), with values of 68–337 for PETRA versus 16–30 for the same regions in the conventional-TE series. Acquisition of series for ultrashort-T 2 * maps was feasible at 1.50 mm isotropic acquisition resolution and TE ≤ 0.58 msec. Strong linear correlations were observed between relaxation rates (R 2 *) and MnCl 2 concentration, and between signal and collagen concentration. Ultrashort-T 2 * signal decay curve fit R 2 and repeatability were high for phantom and knee ultrashort-T 2 * <1 msec. PETRA imaging with minimal artifacts, high SNR, and scan time < 11 minutes was achieved at 7T at high (0.34 mm isotropic) resolution at TE = 0.07 msec and lower resolution (1.52 mm isotropic) at echo times ≤ 0.58 msec. Ultrashort-T 2 * mapping provided acceptable curve-fitting results for substances with sub-millisecond T 2 *.